Coraline - Russell, P. Craig; Gaiman, Neil. (New York : HarperCollins, 2008)
A graphic novel adaptation of the Neil Gaiman story in which Coraline, looking for excitement, ventures through a mysterious door into a world that is similar, yet disturbingly different from her own, where she must challenge a gruesome entity in order to save herself, her parents, and the souls of three others.
"Based on the novel by Neil Gaiman.".
Booklist starred.
Library Journal Starred.
School Library Journal starred.
5.8
3-6
Keywords: Girls -- Comic books, strips, etc. -- Juvenile fiction; Supernatural -- Comic books, strips, etc. -- Juvenile fiction; Cartoons and comics; Fantasy; Girls -- Fiction; Supernatural -- Fiction; Comic books, strips, etc; Fantasy graphic novels; Girls -- Comic books, strips, etc. -- Fiction; Graphic novels; Supernatural graphic novels; Fantasy comic books, strips, etc; Graphic novels